Co-existence of Systemic Lupus Erythematosus and Autoimmune Hypothyroidism (Journal of Armed Forces Medical College, Bangladesh, 2020)
Abstract not AvailableJournal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 1-2